2021
DOI: 10.1089/heq.2020.0130
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Care Provider Attitudes, and Confidence for the Care of Women and Girls Affected by Female Genital Mutilation/Cutting

Abstract: Background: Female genital mutilation/cutting (FGM

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…A key message that these bridging navigators can share with the community is the reassurance that their problems will be resolved, and they will generally be satisfied with care that they can expect from services received, as our study has shown. It is also crucial for healthcare providers to receive iterative training on trauma-informed care approaches, which are culturally informed and linguistically congruent [ 2 , 3 , 16 ]. Training must be extended beyond clinicians to also engage mental health and social service providers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key message that these bridging navigators can share with the community is the reassurance that their problems will be resolved, and they will generally be satisfied with care that they can expect from services received, as our study has shown. It is also crucial for healthcare providers to receive iterative training on trauma-informed care approaches, which are culturally informed and linguistically congruent [ 2 , 3 , 16 ]. Training must be extended beyond clinicians to also engage mental health and social service providers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, it is estimated that approximately 545,000 women and girls have either undergone a form of FGM/C or were born to women from FGM/C-practicing countries [ 1 ]. FGM/C has captured global attention in recent years due to the increasing influx of migrants and refugees to high-income countries where healthcare providers are continually faced with the challenge of providing high quality, culturally sensitive care amidst limited training opportunities on the care of affected women and girls [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for this underutilization is the perception that the topic is too sensitive [ 36 ]. Globally, there is a need for FGM/C specific training for frontline clinical practitioners such as midwives, nurses and physicians to improve their capacity to make correct diagnoses, document, report, treat, and provide psychosexual care [ 41 44 ]. Our previous research has demonstrated that tailoring sexual health training modules or coursework to a Tanzanian setting is an effective strategy for strengthening the understanding, knowledge, and skills of healthcare professionals [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only a few studies [ 46 , 47 , 50 , 51 , 53 , 54 , 60 ] have examined the association between the received training on FGC and the healthcare providers' knowledge or performance of certain FGC-related practices (e.g., identification of FGC cases and notification to child protection authorities). We identified only one [ 60 ] study that has investigated care provision.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only a few studies [ 46 , 47 , 50 , 51 , 53 , 54 , 60 ] have examined the association between the received training on FGC and the healthcare providers' knowledge or performance of certain FGC-related practices (e.g., identification of FGC cases and notification to child protection authorities). We identified only one [ 60 ] study that has investigated care provision. This latter study found a positive association between the healthcare providers' confidence in providing FGC-related healthcare and knowledge of health complications, experience with women with FGC, and more than five years of clinical experience.…”
Section: Introductionmentioning
confidence: 99%